2016
DOI: 10.1038/srep19867
|View full text |Cite
|
Sign up to set email alerts
|

Development and Symbiosis Establishment in the Cnidarian Endosymbiosis Model Aiptasia sp.

Abstract: Symbiosis between photosynthetic algae and heterotrophic organisms is widespread. One prominent example of high ecological relevance is the endosymbiosis between dinoflagellate algae of the genus Symbiodinium and reef-building corals, which typically acquire symbionts anew each generation during larval stages. The tropical sea anemone Aiptasia sp. is a laboratory model system for this endosymbiosis and, similar to corals, produces non-symbiotic larvae that establish symbiosis by phagocytosing Symbiodinium from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 48 publications
2
69
0
1
Order By: Relevance
“…Only recently, a study by Mohamed et al (2016) detected a transient period of differential expression involving a limited number of genes (3% of assayed transcriptome) 4 h after the exposure of Acropora digitifera planula larvae to a competent strain of Symbiodinium. While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016). From the symbiont perspective, apart from the identification of protein kinases that may be involved in the establishment of symbiosis (Rosic et al, 2014), a symbiosisspecific gene was identified in Symbiodinium clade A, an H + -ATPase (Bertucci et al, 2010).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%
“…Only recently, a study by Mohamed et al (2016) detected a transient period of differential expression involving a limited number of genes (3% of assayed transcriptome) 4 h after the exposure of Acropora digitifera planula larvae to a competent strain of Symbiodinium. While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016). From the symbiont perspective, apart from the identification of protein kinases that may be involved in the establishment of symbiosis (Rosic et al, 2014), a symbiosisspecific gene was identified in Symbiodinium clade A, an H + -ATPase (Bertucci et al, 2010).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%
“…Numerous bacterial endosymbionts inhabit eukaryotic hosts that reproduce in a vegetative fashion, such as fungi, ciliated protozoa, and amoebae (which serve as hosts to a broad range of bacteria that also infect plant and animal cells) . In sexually reproducing hosts where germline cells are not infected, endosymbionts are maintained transgenerationally by repeated episodes of infection or phagocytosis . Both bacteria and archaea can become endosymbionts, although the overwhelming majority of reports involve bacteria .…”
Section: Additional Cell Fusions In Evolutionary Historymentioning
confidence: 99%
“…39,40 In sexually reproducing hosts where germline cells are not infected, endosymbionts are maintained transgenerationally by repeated episodes of infection or phagocytosis. 41,42 Both bacteria and archaea can become endosymbionts, although the overwhelming majority of reports involve bacteria. 43 Archaeal endosymbionts have been identified in the cells of an anaerobic marine protist, and much remains to be discovered about other archaeal endosymbionts.…”
Section: Additional Cell Fusions In Evolutionary Historymentioning
confidence: 99%
“…The long-term pairings between cnidarian hosts and eukaryotic dinoflagellate symbionts (family Symbiodinaceae) (LaJeunesse et al, 2018) are evolutionarily ancient and highly specific (Coffroth et al, 2010;Hambleton et al, 2014;LaJeunesse et al, 2004); yet cnidarians also phagocytose inert beads (Bucher et al, 2016), associate transiently with heterologous symbiont strains (Dunn and Weis, 2009;Hambleton et al, 2014;Matthews et al, 2017;Wolfowicz et al, 2016), and with Chromera velia, a chromerid microalga that is closely related to apicomplexan parasites (Cumbo et al, 2013;Mohamed et al, 2018). Unlike true symbionts, however, these non-symbiotic microalgae fail to engage in lasting relationships with their host.…”
Section: Phagocytosis Of Microalgae From the Environment Is Primarilymentioning
confidence: 99%
“…To gain insight into the mechanisms that support intracellular maintenance of symbionts and removal of non-symbiotic microorganisms, we exploited the ability of naturally aposymbiotic (symbiont-free) Aiptasia larvae to phagocytose symbionts from the environment (Bucher et al, 2016;Hambleton et al, 2014;Wolfowicz et al, 2016). We screened seven distinct microalgae from four phyla ( Fig.…”
Section: Phagocytosis Of Microalgae From the Environment Is Primarilymentioning
confidence: 99%